2001
DOI: 10.1096/fj.00-0675fje
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a tumor‐suppressive compound from grapes, induces apoptosis via a novel mitochondrial pathway controlled by Bcl‐2

Abstract: We report that resveratrol (3,5,4'-trihydroxy-trans-stilbene), a phytoalexin found in grapes and other plant food, induced a breakdown of the mitochondrial transmembrane potential (∆Ψ m ) in T-acute lymphoblastic leukemia cells and swelling of isolated rat mitochondria. The breakdown of ∆Ψ m was accompanied by the production of reactive oxygen species (ROS), and preceded phosphatidylserine exposure and DNA fragmentation. Breakdown of ∆Ψ m was not caused by the activation of caspase-8 or Bid, as no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
121
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 48 publications
12
121
0
Order By: Relevance
“…Particularly, by acting as antioxidant, anti-mutagen as well as by inducing phase II drug-metabolizing enzymes, trans-resveratrol inhibits the initiation phase of tumorigenesis; concomitantly, it mediates the anti-inflammatory response and induces cell differentiation, thereby inhibiting tumor promotion and progression, respectively [28]. Subsequently, other groups reported the anti-proliferative and pro-apoptotic activity of trans-resveratrol in several tumor cell lines [2,27,41,56], suggesting that it can function by modulating and interacting with a broad range of cellular targets, ranging from cell surface receptors [5,7] to caspases [43]; from mitochondria [8] and mitochondria-associated proteins [43,50,60], to intracellular protein kinases, such as protein kinase B (PKB)/Akt, PKC, MAP kinases [34,57,58,62,65] and transcription factors (e.g. p53, pRb, c-Jun and NF-jB) [30,37,45,59].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, by acting as antioxidant, anti-mutagen as well as by inducing phase II drug-metabolizing enzymes, trans-resveratrol inhibits the initiation phase of tumorigenesis; concomitantly, it mediates the anti-inflammatory response and induces cell differentiation, thereby inhibiting tumor promotion and progression, respectively [28]. Subsequently, other groups reported the anti-proliferative and pro-apoptotic activity of trans-resveratrol in several tumor cell lines [2,27,41,56], suggesting that it can function by modulating and interacting with a broad range of cellular targets, ranging from cell surface receptors [5,7] to caspases [43]; from mitochondria [8] and mitochondria-associated proteins [43,50,60], to intracellular protein kinases, such as protein kinase B (PKB)/Akt, PKC, MAP kinases [34,57,58,62,65] and transcription factors (e.g. p53, pRb, c-Jun and NF-jB) [30,37,45,59].…”
Section: Introductionmentioning
confidence: 99%
“…The pro-apoptotic members of the Bcl-2 family known as BH3-only proteins behave as sensors of cellular damage and initiate the death process by either inhibiting anti-apoptotic members of the family or activating another group of proapoptotic, Bcl-2-related proteins, the Bax/Bak proteins, through induction of conformational changes (14). Various reports have shown that resveratrol could induce apoptosis of tumor cells through a mitochondrial-dependent pathway that partially depended on Bax conformational changes and cellular redistribution (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…It is expected that modulators of apoptosis with different mechanisms of action independent of the classical apoptotic signaling cascade may have promising features of bypassing clinical drug resistance caused by impaired apoptotic signaling. Indeed, there are reports of cytochrome c-independent cell death induced by resveratrol that is not completely prevented by Bax deficiency, suggesting the complex nature of death signaling induced by resveratrol (25,26). Processing of caspases independent of cytochrome c in certain cellular systems (25) and marked caspase-8 activation independent of classical death receptors (27, 28) add more credibility to the notion that resveratrol-mediated apoptosis involves more complex signaling events than the conventional pathways of apoptosis triggered by other known antitumor agents.…”
mentioning
confidence: 99%